1999
DOI: 10.1002/(sici)1521-3927(19990401)20:4<203::aid-marc203>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Styrene-vinylferrocene random and block copolymers by TEMPO-mediated radical polymerization

Abstract: SUMMARY: TEMPO-mediated free radical polymerization was employed for homo-and copolymerization of vinylferrocene (Vfc). Homopolymerization of Vfc resulted in relatively narrow polydispersities (M

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…[90][91][92][93][94][95][96][97][98][99] In 1999, Frey and coworkers reported the copolymerization of vinylferrocene with styrene using the ''living'' radical initiator 2,2,6,6-tetramethyl-1-pyperidinyl-1-oxy (TEMPO). [100] These reactions resulted in the production of block copolymers with narrow polydispersities.…”
Section: Polymerization Of Olefin-functionalized Metallocenessupporting
confidence: 90%
“…[90][91][92][93][94][95][96][97][98][99] In 1999, Frey and coworkers reported the copolymerization of vinylferrocene with styrene using the ''living'' radical initiator 2,2,6,6-tetramethyl-1-pyperidinyl-1-oxy (TEMPO). [100] These reactions resulted in the production of block copolymers with narrow polydispersities.…”
Section: Polymerization Of Olefin-functionalized Metallocenessupporting
confidence: 90%
“…This renders them very interesting in this field of science, and therefore the development of ferrocenyl-containing block-copolymers has become an important issue [7][8][9][10]. The corresponding methods developed by Nuyken et al and Frey et al are based on the controlled anionic and radical polymerization, respectively, and were successfully applied for the copolymerization of vinylferrocene with styrene or other olefinic monomers [11,12]. Balsara et al showed that a poly(vinylferrocene)-b-poly(isoprene) block-copolymer can be successfully applied as heterogeneous catalyst for Michael additions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Baumert et al employed TEMPO‐mediated free radical polymerization to synthesize a homopolymer of vinyferrocene and a copolymer of vinyferrocene with styrene, as shown in Scheme . Experimental results showed that molecular weight of the homopolymer of vinylferrocene was limited to 4.8 × 10 3 g mol −1 , while the molecular weight of the copolymer was up to 1.0 × 10 4 g mol −1 .…”
Section: Synthesis Of Ferrocene‐containing Polymers and Derivatives Umentioning
confidence: 99%